The Effect of Competence and Placement on the Performance of Civil Servants in Pamekasan Regency - Fitriya Dwi Anggraini; Helmi Buyung Aulia; Yahya Surya Winata (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
Human resources are the drivers of activities within the company. Every organization needs to pay attention to the management of human resources both competence, the process of placing employees which will later increase productivity in achieving the goals expected by the company. In 2021 the central government implemented a policy related to a major overhaul of the structural position changes of echelons III and IV in government agencies. The policy is implemented nationally so that the Pamekasan Regency government is also obliged to equalize structural positions to functional positions.The research method used is quantitative. The sample of this study amounted to 73 echelon IV civil servants who were appointed from structural positions into functional positions. The analysis used is multiple linear analysis. The purpose of this study is to determine whether competence and placement affect the performance of civil servants in Pamekasan Regency. The results showed that partially competence had a positive and significant effect on the performance of civil servants in Pamekasan Regency, placement did not have an effect and was significant but had a positive value on the performance of civil servants in Pamekasan Regency. However, simultaneously competence and placement have a positive and significant effect on the performance of civil servants in Pamekasan Regency.